2019
DOI: 10.1108/jmd-01-2019-0030
|View full text |Cite
|
Sign up to set email alerts
|

Talent management practices: perceptions of academics in Egyptian public business schools

Abstract: Purpose The purpose of this paper is to focus on 3 out of 24 business schools in Egypt in order to investigate their talent management practices of academics. Design/methodology/approach A total of 350 academics were contacted and 245 of them were interviewed in 49 face-to-face focus groups. The interview length for each focus group is about 45 min and is conducted in Arabic, the mother tongue of all respondents. Upon conducting the interviews, the authors used thematic analysis to determine the main ideas i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 64 publications
1
34
0
1
Order By: Relevance
“…Morphet (2008) highlights that new governance structure, funding possibilities, and mechanisms of service delivery that the public sector emphasize have reframed public servants' job responsibilities, duties, and tasks. This may justify why concepts such as work/life balance and workplace happiness have started to find a space on the work practices done by public administration personnel (Mousa, 2018;Mousa et al, 2019b). Accordingly, the author of this paper recommends that the administration of public universities also to pay more attention to the level of happiness their academics experience.…”
Section: Discussionmentioning
confidence: 99%
“…Morphet (2008) highlights that new governance structure, funding possibilities, and mechanisms of service delivery that the public sector emphasize have reframed public servants' job responsibilities, duties, and tasks. This may justify why concepts such as work/life balance and workplace happiness have started to find a space on the work practices done by public administration personnel (Mousa, 2018;Mousa et al, 2019b). Accordingly, the author of this paper recommends that the administration of public universities also to pay more attention to the level of happiness their academics experience.…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrate that the manner in which employees perceive the way talent management practices are applied in their respective organisations would determine their intention to stay or leave the organisation and this holds true for the nurses in public hospitals (Mousa and Ayoubi, 2019;Ramli et al, 2018). Furthermore, in the healthcare contexts, studies have undeniably demonstrated that there is a growing realisation of the poorly developed scope and shortage of empirical studies on the topic of talent management (King, 2015;Mousa and Puhakka, 2019).…”
Section: Ajems 123mentioning
confidence: 99%
“…Mukweyi (2016) conducted a study on influence of talent management practices on retention of healthcare professionals in Kenya mission hospitals, and the results showed that talent management practices had positive impact on retention of health worker employees. Mousa and Ayoubi (2019) analysed the implementation of talent management practices in Slovak healthcare sector, where the results revealed that the size of the organisation had an impact on the application of talent management processes and practices. Surprisingly, it was also observed that the situation in Slovak healthcare organisations was not ideal as the healthcare employers paid very little attention to creation of policies that encouraged career growth and development opportunities.…”
Section: Talent Management In Healthcare Institutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Talent management that encourages employee satisfaction prevents competent employees from leaving the organisation as this could have adverse effects on performance and service delivery (Hafez, AbouelNeel, & http://www.sajhrm.co.za Open Access Elsaid, 2017;Ozuem, Lancaster, & Sharma, 2016). This is inconsonant with the international nursing literature that views job satisfaction as a major contributory factor for employees' intent to stay (Crowley-Henry, Benson, & Al Ariss, 2018;Mousa & Ayoubi, 2019).…”
Section: Introductionmentioning
confidence: 99%